2021
DOI: 10.1016/j.jamcollsurg.2021.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Care Fragmentation and Mortality in Readmission after Surgery for Hepatopancreatobiliary and Gastric Cancer: A Patient-Level and Hospital-Level Analysis of the Healthcare Cost and Utilization Project Administrative Database

Abstract: BACKGROUND: Hepatopancreatobiliary (HPB) and gastric oncologic operations are frequently performed at referral centers. Postoperatively, many patients experience care fragmentation, including readmission to “outside hospitals” (OSH), which is associated with increased mortality. Little is known about patient-level and hospital-level variables associated with this mortality difference. STUDY DESIGN: Patients undergoing HPB or gastric oncologic surgery we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…16 We also examined several clinical outcomes including 90day postoperative mortality, which was selected as it is likely a downstream consequence applicable across all surgical specialties if a patient were to experience inadequate care, triage, or failure to rescue on the basis of the initial site of acute care presentation. 11 Chi-square or Wilcoxon Mann-Whitney tests were used for between-group differences. Hierarchical modeling with random effects at the level of each geographic region was used to account for possible unmeasured patient and facility differences between the geographic regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 We also examined several clinical outcomes including 90day postoperative mortality, which was selected as it is likely a downstream consequence applicable across all surgical specialties if a patient were to experience inadequate care, triage, or failure to rescue on the basis of the initial site of acute care presentation. 11 Chi-square or Wilcoxon Mann-Whitney tests were used for between-group differences. Hierarchical modeling with random effects at the level of each geographic region was used to account for possible unmeasured patient and facility differences between the geographic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients often receive oncologic surgery at centralized facilities because of well-established relationships between volume and outcomes, [4][5][6][7][8][9][10] but an extensive body of literature has shown that a high percentage of surgical patients are evaluated, readmitted, and cared for at local facilities other than where the site of their initial operation and that this form of fragmented care is associated with worse shortand long-term outcomes. [11][12][13][14] Innovative models of care delivery are needed to address the gap between centralized oncologic surgeries and decentralized fragmented postoperative acute care.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies did not find an effect on mortality despite the association of fragmented care with treatment delay (Abelson et al, 2021). Moreover, fragmented care‐related factors, including distance for travel, were not significantly associated with increased patient readmission‐associated mortality (Brauer et al, 2021). Although a relationship between fragmented care and patient outcomes has not been observed, fragmented care may cause treatment delays in patients with cancer (Abelson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The present study used propensity score matching to control for confounding (49). Matching algorithms were selected through an iterative process that made it possible to select the algorithm that produced the best balance of the baseline variables.…”
Section: Discussionmentioning
confidence: 99%